Nucleus-Nucleus Effects in Fully Differential Cross Sections for Energetic C6＋＋He Collisions with Small Momentum Transfer - 陆晨文 安文芳 孙世艳 贾祥富 (中国物理快报：英文版, 2015)
The modified Coulomb-Born approximation with and without the internuclear interaction （MCB-NN and MCB） is used to calculate the fully differential cross sections （FDCS） for the single ionization of helium by lOO MeV/amu C6＋ impact. The effects of the internuclear interaction on the FDCS are examined in geometries. The results are compared with experimental data and theoretical predictions from a three-body distorted-wave （3DW） model and a time-dependent close-coupling model. It is shown that the present MCB-NN results are in good agreement with the experiments in the scattering plane and the MCB results qualitatively reproduce the experimental structure outside the scattering plane. In particular, the MCB theory predicts the ＇double-peak＇ structure in the perpendicular plane.